A Look Back: A chronicle of Kappan's coverage of the reading wars. (May 2022) - Preston, Teresa
Reading instruction has been the subject of significant controversy for more than five decades, and Kappan has allowed advocates of many different types of reading instruction to make their cases in the magazine's pages. Teresa Preston chronicles the history of the reading wars as they played out in Kappan. Researchers and scholars have debated the merits of phonics, wholeword, and whole-language approaches to reading, as well as the nature of research and instruction in general. But some have wondered how valuable the debate is to educators looking for guidance to help the children in their districts and schools .